Tetradentate schiff base copper(II) complexes - Felicio, Roberto C.; Silva, Gislaine A. da; Ceridorio, Lucinéia F.; Dockal, Edward R. (Taylor & Francis, 1999)
Ten copper(II) complexes of tetradentate Schiff bases obtained by condensing two moles of an o-hydroxyphenylcarbonyl compound with a diamine have been prepared and characterized by elemental analyses, melting points, IR and electronic spectra. The IR and electronic spectra of the free ligand and the complexes are compared and discussed. The deconvolution of the visible spectra of the complexes in CHCl3, approximately C2v or C1, yielded four peaks at ca. 15000, 17000, 18000-19000, and 20000-22000 cm-1, assigned to the four d-d transitions.